2011
DOI: 10.1158/0008-5472.can-10-3453
|View full text |Cite
|
Sign up to set email alerts
|

Steroid Receptor Coactivator-1 Upregulates Integrin α5 Expression to Promote Breast Cancer Cell Adhesion and Migration

Abstract: Metastatic breast cancer remains a lethal disease with poorly understood molecular mechanisms. Steroid receptor coactivator-1 (SRC-1 or NCOA1) is overexpressed in a subset of breast cancers with poor prognosis. It potentiates gene expression by serving as a coactivator for nuclear receptors and other transcription factors. We previously reported that SRC-1 promotes breast cancer metastasis without affecting primary mammary tumor formation. Herein, we found that SRC-1 deficiency in mouse and human breast cancer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
75
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(77 citation statements)
references
References 50 publications
2
75
0
Order By: Relevance
“…In the present study, ITGA5 was also found to be associated with pathways involved in focal adhesion and ECM-receptor interaction. Focal adhesion connects the cell cytoskeleton and the ECM through integrins (33). Accordingly, ITGA5 exhibited a crucial role in the OS development via cell adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, ITGA5 was also found to be associated with pathways involved in focal adhesion and ECM-receptor interaction. Focal adhesion connects the cell cytoskeleton and the ECM through integrins (33). Accordingly, ITGA5 exhibited a crucial role in the OS development via cell adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike other oncogenes, recent studies provide evidence of a specific role for SRC-1 in the development of metastasis (29,30). Of interest, knockdown of SRC-1 can decrease cell proliferation, restore differentiation, and decrease migration in tamoxifen-resistant breast cancer cells (11).…”
Section: Discussionmentioning
confidence: 99%
“…Among these we should mention NCOA1 (nuclear receptor coactivator (1), a transcriptional coactivator belonging to the SRC family which is deregulated in breast and prostatic cancer and may potentiate gene expression by acting as a coactivator for nuclear hormone receptors and other transcription factors (TF) [44][45][46][47][48][49][50][51][52][53][54][55]; and ROCK2, a serine/threonine kinase member of the Rho pathway, involved in cell adhesion, migration, invasion, and mitosis [56][57][58][59], which may be a potential therapeutic target in human cancer cells and animal models [60][61][62][63][64][65][66][67][68].…”
Section: Discussionmentioning
confidence: 99%